Degrees of Hypothesis, Scale of Conditions - Achard-Bayle, Guy (Verbum, 2024)
In many languages, there is a wide variety of words and expressions for hypothesis. The result is a diversity of interpretations linked to the use of these words or expressions: “hypothetical”, “false con-ditional”, “concessive”, “oppositive”, “explanatory”, and this tradition is perpetuated in today’s grammars. Following in the footsteps of others, we have studied this diversity, seeking however to bring interpreta-tions together under the umbrella of the suspension of truth (vericonditionality) for dialogical debate (veri-dictionality), thus moving from the fact represented to the fact of saying. Here, we take another look at the diversity of introducers, constructions, tenses and modes. Faced with a plethora of combinations, and as soon as we move away from the potential/actual, possible/counterfactual opposition, we can envisage not an opposition but a scale, a gradation of confidentiality or hypothesis of combinations that envisage or allow, or not, actualization.